2019
DOI: 10.3989/ic.67222
|View full text |Cite
|
Sign up to set email alerts
|

Aplicación de un modelo Lean-BIM para la mejora de la productividad en redacción de proyectos de edificación

Abstract: El presente trabajo propone un modelo para la mejora del rendimiento de la redacción de proyectos de edificación en BIM. La productividad del sector de la construcción es una materia que preocupa y genera debates acerca del modelo de producción adecuado para mejorar su rendimiento. Si se compara el nivel de productividad de la construcción con otros sectores, tales como la industria o el automóvil, resulta bajo, y la evolución de los últimos años evidencia un incremento de esta diferencia. Se pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 9 publications
0
11
0
6
Order By: Relevance
“…La metodología VDC desde un enfoque norteamericano se apoya de tres componentes (PPM, BIM y ICE) (Figura 4), por otro lado, la metodología BIM desde un enfoque europeo se apoya de (procesos, tecnología y personas) (14), ambas son equivalentes y buscan el mismo objetivo (15).…”
Section: Virtual Design Construction (Vdc)unclassified
See 1 more Smart Citation
“…La metodología VDC desde un enfoque norteamericano se apoya de tres componentes (PPM, BIM y ICE) (Figura 4), por otro lado, la metodología BIM desde un enfoque europeo se apoya de (procesos, tecnología y personas) (14), ambas son equivalentes y buscan el mismo objetivo (15).…”
Section: Virtual Design Construction (Vdc)unclassified
“…Los profesionales ligados a la industria AEC, están adoptando nuevos modos de intercambio de información interdisciplinaria, aplicando diversas metodologías emergentes y de rápido crecimiento tales como Integrated Project Delivery (siglas IPD en inglés) como compañero de BIM (6,11,12) y Lean Construction (siglas LC en inglés) (13,14). También surge la metodología VDC desde un enfoque norteamericano (15), desarrollado por CIFE de la Universidad de Stanford en California, USA; como la forma más precisa de obtener proyectos de alta calidad (16).…”
Section: Introductionunclassified
“…Thus, BIM methodology plays a fundamental role in the design context and has the potential to completely transform the AECO industry, facilitating the identification of potential problems in early stages prior to project execution [7]. BIM can be used to visualize, coordinate, and ultimately improve the work and productivity of the entire industry [8]. However, the AECO industry currently uses the BIM methodology in a rudimentary and unstandardized way, missing out on the full potential of its benefits [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, studies were also found which analyze the synergy of LPS and BIM together (16)(17)(18)(19)(20) and even studies which analyze case studies where these tools have been used (21)(22)(23). These studies conclude that the use of both tools would lead to a true revolution and an evolutionary leap which would contribute towards increasing the success of the projects managed in accordance with the project management best practices that have been being applied in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, and regarding the studies analyzed in the article, only few of them are written by Spanish authors (20,24,26) but none of them identify the obstacles or Best Practices (BP) to be implemented in relation to the LPS in Spain. As such, the present article has the following objectives:…”
Section: Introductionmentioning
confidence: 99%